Pengaruh Rasio Keuangan, Firmsize dan Makroekonomi Terhadap Return Saham: - - Hari Sasmito (Politeknik Ganesha Medan, 2023)
The purpose of the study was to analyze the effect of financial ratios such as CR, ROA, FATO, DAR, PER combined with, Firmsize, and macroeconomics such as Inflation and BI interest rates on stock returns. The method used is a quantitative method with data analysis techniques using multiple linear regression. The research population was 80 real estate and property companies listed on the IDX in 2018 - 2022 and obtained a sample of 27 companies determined using purposive sampling method. Overall the results reveal that the independent variables have an impact on stock returns, then the ROA and PER variables have a significant positive correlation with stock returns. The results also show that the Firmsize and Interest rate variables are negatively correlated with stock returns while CR, FATO, DAR and Inflation actually have no effect on stock returns.